Hypoxia Increases the Tempo of Phage Resistance and Mutational Bottlenecking of Pseudomonas aeruginosa - Schumann, Ashley R.; Sue, Andrew D.; Roach, Dwayne R. (Frontiers in Microbiology, 2022)
Viruses that infect bacteria (i.e., phages) are abundant and widespread in the human body, and new anti-infective approaches such as phage therapy are essential for the future of effective medicine. Our understanding of microenvironmental factors such as tissue oxygen availability at the site of phage–bacteria interaction remains limited, and it is unknown whether evolved resistance is sculpted differentially under normoxia vs hypoxia. We therefore analyzed the phage-bacteria interaction landscape via adsorption, one-step, time kill dynamics and genetic evolution under both normoxia and hypoxia. This revealed that adsorption of phages to Pseudomonas aeruginosa decreased under environmental 14% oxygen (‘hypoxia’), but phage time-kill and one-step growth kinetics were no further influenced. Tracking the adaptation of P. aeruginosa to phages uncovered a higher frequency of phage resistance and constrained types of spontaneous mutation under hypoxia. Given the interest in developing phage therapies, developing our understanding of phage–pathogen interaction under microenvironmental conditions resembling those in the body offers insight into possible strategies to overcome multidrug-resistant bacteria.